LEGAL PROTECTION IN BANKS FOR DISCLOSING BANK CONFIDENTIALITY RELATED TO THE CRIME OF MONEY LAUNDERING - Tjoeng Sinta Pertiwi Sandjaja; Siti Marwiyah; Subekti Subekti (Jurnal Ekonomi, 2023)
Bank runs business with fiduciary principle, prudential, know your customer and bank secrecy. The money laundering criminal can use bank to save fund. Bank as a financial institute must implements prudential and must keep customer personal information has polemic and must open bank secrecy if money laundering occurred. That’s matter become problem is regulation and impelementation of regulation about bank secrecy and law protection for banking and customer because open customer personal information because of money laundering. This riset use normative law riset with statue approach use law material source. Statue approach use with study all regulation. The type of data used is in the form of data obtained from laws and regulations, books, journals, library materials and other written sources related to the problem to be studied. To analyze the data collected from literature search, this research uses qualitative analysis techniques.